PREVALENSI PENURUNAN TAJAM PENGLIHATAN PADA SISWA KELAS 3-6 SEKOLAH DASAR NEGERI 1 MANGGIS, KARANGASEM BALI TAHUN 2014 - Witantra Dhamar Hutami; Putu Asti Wulandari (DiscoverSys Inc., 2016)
Background: Visual disturbance in school children can have impacts on long term health status, school performance, and emotional and social development of those children. Despite these facts, there are only few eye examinations performed to assess disturbance of visual acuity in elementary school children. This research aims to observe the prevalence of decreased visual acuity in 3rd-6th grade students of Manggis 1 State Elementary School, District of Manggis, Karangasem Regency, Bali Province year 2014.Method:This Study is a descriptive cross-sectional study with the sample of 120 school children from 3rd â€“ 6th grade students of Manggis I State Elementary School. Data were collected from visual acuity examination using Snellen Chart at the distance of 6 metres and from interview guided by questionnaire form.Â Result:The prevalence of decreased visual acuity in both right and left eyes of 3rdâ€“6th grade students of Manggis 1 State Elementary School is 70%. The values of decreased visual acuity of the subjects studied vary in the range of 6/30 up to 6/9. The majority of students found to have decreased visual acuity have a mild decreased visual acuity, and are found in the right eyes of 46 students (38,3%) and in the left eyes of 47 students (39,2%). There are some factors that tend to influence the value of visual acuity, they are duration of watching television, reading position, and duration of playing outdoor.Conclusion: There are some students of manggis 1 elementary school who suffer from unrecognized decreased visual acuity. Their parents are advised to bring their children to the nearest eye health care center to examine the visual acuity in order to acquire proper management regarding their decreased visual acuity.